Sistem Pengendalian Otomatis Pada Budidaya Sarang Burung Walet Menggunakan Internet of Things - Ahmad Zamahuri (Politeknik Negeri Malang, 2019)
In swallow nest cultivation, swallow breeders still have difficulty in tropical climates, one of which is maintaining the temperature and humidity in the swallow nest room to be stable and to know the value of swallow population. When the temperature is hot, the swallow room will become dry which impacts on the nest is damaged and the swallow is not comfortable living there. Therefore, a system that can be easily managed by swallow farmers is made so it can help reduce hot temperature and lack of humidity in the swallow nest room by using a sprayer that works automatically. In this system, there are temperature and humidity detection module which functions to detect the temperature valueand humidity when the room is hot / dry, the detected value will be processed by the microcontroller so that it gives an active sprayer command if the room temperature is hot, while the swallow detection module that uses infrared sends the movement value if there is a moving object. The value of the system will be sent to a cloud database which will be conveyed via the farmer wallet smartphone application. The accuracy level of the infrared detector sensor module and the air humidity sensor is very good, so that it can control the temperature conditions in the swallow room which is 27 degrees C and a stable humidity at a value of 80%. The stability of temperature and humidity produces swallow nests which have high selling value.